Anatomy, stretching & training for cyclists. A step-by-step guide to getting the most from your bicycle workout - Purchell, L. (Skyhorse Publ., 2014)
Every year, more and more people take up cycling to get in shape and stay fit. Thousands of people are buying new bikes with the latest technology, entering races, and even forgoing rush hour traffic and crowded public transportation to ride to work. But the joy and thrill of cycling are often marred by injuries that can bother you for a few weeks or for years. That`s why every cyclist needs to have Anatomy, Stretching & Training for Cyclists. Lisa Purcell includes a detailed exercise program that is designed for cyclists from beginner to advanced levels and that is devised to strengthen and stretch the major muscle groups used in cycling. She provides answers and tools for training, including: